A novel PAX1 null homozygous mutation in autosomal recessive otofaciocervical syndrome associated with severe combined immunodeficiency. Issue 6 (24th October 2017) - Paganini, I.; Sestini, R.; Capone, G.L.; Putignano, A.L.; Contini, E.; Giotti, I.; Gensini, F.; Marozza, A.; Barilaro, A.; Porfirio, B.; Papi, L.
Abstract : Otofaciocervical syndrome (OFCS) is a rare disorder characterized by facial anomalies, cup‐shaped low‐set ears, preauricular fistulas, hearing loss, branchial defects, skeletal anomalies, and mild intellectual disability. Autosomal dominant cases are caused by deletions or point mutations of EYA1 . A single family with an autosomal recessive form of OFCS and a homozygous missense mutation in PAX1 gene has been described. We report whole exome sequencing of 4 members of a consanguineous family in which 2 children, showing features of OFCS, expired from severe combined immunodeficiency (SCID). To date, the co‐occurrence of OFCS and SCID has never been reported. We found a nonsense homozygous mutation in PAX1 gene in the 2 affected children. In mice, Pax1 is required for the formation of specific skeletal structures as well as for the development of a fully functional thymus. The mouse model strongly supports the hypothesis that PAX1 depletion in our patients caused thymus aplasia responsible for SCID. This report provides evidence that bi‐allelic null PAX1 mutations may lead to a multi‐system autosomal recessive disorders, where SCID might represent the main feature. Abstract : Segregation of a novel PAX1 mutation in a highly consanguineous family. The 2 homozygous children showed otofaciocervical syndrome and severe combined immunodeficiency, while heterozygous family member presented preauricular pits.